STRATEGIES FOR REDUCING STUTTERING THROUGH THE DEVELOPMENT OF SPEECH CONFIDENCE - Abdullayeva Karomat Islom qizi (MULTIDISCIPLINARY JOURNAL: FUNDAMENTAL RESEARCH SCIENTIFIC JOURNAL, 2025)
Abstract: This article examines strategies for reducing stuttering in children and adolescents by developing speech confidence. The study explores how building self-assurance in verbal communication can decrease anxiety, improve fluency, and enhance overall communicative competence. Techniques such as guided practice, positive reinforcement, role-playing, and cognitive-behavioral interventions are highlighted as effective methods for fostering speech confidence. The research emphasizes that integrating confidence-building strategies into speech therapy can create a supportive environment, promote motivation, and lead to sustainable improvements in speech fluency.